Pastoral Konseling Discipleship-Based Counseling for Terminal Patient: A Supportive and Empowerment Care - Twin Hosea Widodo Kristyanto; Rikardo P. Sianipar (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
Terminal illness is an illness that cannot be cured or treated adequately which is expected to cause death. Patients with terminal illness can be called terminal patients. The fact that terminal patients are being threatened by death can affect their quality of life. Terminal patients need medical and palliative care. Palliative care that can be provided to patients are psychological services which include spiritual support, including pastoral counseling. Thus, this paper aims to discuss the role of discipleship-based pastoral counseling in helping to solve problems caused by illness faced by terminal patients. Qualitative methods are used in answering the objectives of this study. The approach used was a literature study and phenomenological analysis of one source (AS) who is a counselor from the Yayasan Sahabat Orang Sakit. The results showed that pastoral counseling for terminal patients needs to focus on the area: the patient's regression condition and preparing to face death. In discipleship-based counseling, terminal patients are discipled from stage to stage so that the patient can finally serve fellow terminal patients. That's when the terminal patients can understand that their life can still be a blessing to others, and God has been proven to bring goodness in his life.